2006
DOI: 10.1227/01.neu.0000220089.39533.4e
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of True In Vivo (Application) Accuracy in Cranial Image-guided Surgery: Influence of Mode of Patient Registration

Abstract: Not surprisingly, application accuracy of image-guidance is worse without implanted cranial markers. Unexpectedly, there was no major difference in localization of deep targets between the other registrations tested in this study. Care must be taken when using image-guidance tools to consider error introduced by registration. Cranium-implanted fiducials should be considered when high accuracy and reproducibility are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 9 publications
5
73
0
Order By: Relevance
“…Dorward et al [27] found a euclidean error of 4.8 mm in the in vivo arm of their study. Mascott et al [26] report mean localization errors between 3.3 and 5.4 mm. One relatively recent comparative phantom study actually found a smaller euclidean error in a frameless system when a specific planning and targeting protocol was used (probe's eye) [28].…”
Section: Frameless Stereotaxy: a Hypothetical Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorward et al [27] found a euclidean error of 4.8 mm in the in vivo arm of their study. Mascott et al [26] report mean localization errors between 3.3 and 5.4 mm. One relatively recent comparative phantom study actually found a smaller euclidean error in a frameless system when a specific planning and targeting protocol was used (probe's eye) [28].…”
Section: Frameless Stereotaxy: a Hypothetical Cohortmentioning
confidence: 99%
“…RMS gives no information regarding the correspondence of those coordinates to the actual location of objects in physical space. This concept was elegantly demonstrated by Mascott et al who found no statistically significant correlation of RMS values with the accuracy of marker placement in a large in vivo study [26]. Studies using phantom models typically measure the mean error of localization, which represents the average magnitude of the distance between the probe and its intended target.…”
Section: Frameless Stereotaxy: a Hypothetical Cohortmentioning
confidence: 99%
“…This method is currently the "gold standard" for image-tophysical rigid registration. [3][4][5] A more unusual alternative is the use of cortical surface landmarks whereby vessel bifurcations identified on the patient's brain and within MR images are used to determine correspondence. 6 While PBR is standard in most of today's ORs, other techniques have also been pursued that use surface contour data to achieve a MRsurface to patient-surface registration.…”
Section: Introductionmentioning
confidence: 99%
“…There are two primary issues of concern: (1) the difference between target registration and accuracy at the skull base and (2) the lack of real-time intraoperative feedback. 15,16 The shortcomings of applying traditional neuronavigational systems to the skull base, particularly the temporal bone, have been addressed in the literature. Previous studies have demonstrated that registration error does not necessarily correlate with actual anatomic accuracy or global accuracy at the skull base.…”
Section: Current Neuronavigational Systems and Skull Base Surgerymentioning
confidence: 99%